Effect of interval between follicular recruitments on superovulatory response in non-lactanting Holstein cows - Suntos, R. M.; Vasconcelos, J. L. M. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2007)
Dry Holstein cows were synchronized by a modified Ovsynch protocol. On day 7 (day 0 = day of the second GnRH), group 7 (G-7; n=19) received an used CIDR and GnRH (100 mu g). Group 14 (G-14,n=21) received an used CIDR and PGF2 alpha (25mg). On day 14, the dominant follicle (DF) was removed, by aspiration: the used CIDR was changed for a new CIDR plus PGF2a Thirty-six hours later, the FSH treatment was initiated. On the seventh injection of FSH, the CIDR was removed Thirly-six hours after, the cows received GnRH. Donors were inseminated 12 and 24h after the GnRH injection. Embryos were recovered seven days after Al. The DF diameter in G-7 was 13. 1mm on day 7 and 11.2mm on day 14. The persistent DF in the G-14 increased from 12.6mm on day 7 to 16.4mm on day 14 (P < 0.001). The number of follicles >= 8mm, 48h after the beginning of the FSH treatment, was 15.6 in G-7 and 12.5 in G-14,effects were detected on number of corpus luteum and embryos. The shorter (P < 0.05). No treatment of interval between follicular recruitment the higher the number of recruited follicles, but it did not have effects on the number or quality of embryos produced.
Keywords: dairy cow; follicular ablation; embryo; FSH; superovulation